Critical Analysis of Anti-Slapp Regulations in The Field of Criminal Law in Indonesia - Ahmad, Gelar Ali (Golden Ratio of Law and Social Policy Review, 2024)
This study examines the issue of SLAPP (Strategic Lawsuit Against Public Participation) and the appropriate Anti-SLAPP legal protections for environmental activists in Indonesia. It highlights how SLAPP serves as a tool for corporations to intimidate and silence environmental activists who oppose practices detrimental to society and the environment, particularly those resulting from the exploitation of natural resources. This study critically analyzes the existing Anti-SLAPP regulations in Indonesia, particularly within the context of criminal law, as outlined in various regulations. The study identifies significant shortcomings in these regulations, such as the lack of clear definitions of environmental activism, bureaucratic obstacles in seeking protection, and insufficient coverage throughout the entire criminal process. The results indicate that while legal protection for environmental activists is in place, it remains partial and inadequate, necessitating a more integrated and robust regulatory framework to better protect the rights and activities of environmental activists. This study offers suggestions for harmonizing Anti-SLAPP regulations across relevant legal institutions to ensure consistent and reliable protection for environmental activists.